Exploring exercise adherence and quality of life among veteran, novice, and dropout trainees - Gabay, Maor; Levi, Ofer; Petracovschi, Simona; Negrea, Cristian; Matichescu, Marius; Oravitan, Mihaela (Frontiers in Sports and Active Living, 2023)
Introduction The purpose of this study was to identify and reveal the different contexts, variables, and factors that may influence adherence to physical activity among veteran, novice, and dropout trainees, such as the frequency of the weekly training units, the trainees preferred type of exercise, the purpose of the physical activity, and the relationship between support and supervision by fitness instructors and professionals. This study also examined the relationships between trainees, seniority and the strength of the habit and adherence to physical activity, the effects of personal variables such as age and gender on adherence to physical activity, and how the seniority and adherence of trainees may affect their quality of life. Methods A total of 460 participants drawn from the broader Israeli exercise community, which encompasses a diverse range of individuals within the general adult population, were engaged in this study. These participants included seasoned exercisers, individuals who had recently initiated exercise routines, and those who had previously engaged in physical activity. Each participant completed a comprehensive set of questionnaires, including the Self-Report Habit Index, the Exercise Adherence Rating Scale, and the World Health Organization (WHO) Quality of Life Scale. In addition to the questionnaire responses, demographic data and inquiries concerning their physical activity were also collected. Results The results show that the average frequency of the weekly training units of veteran trainees was significantly higher than that of novice trainees: 3.95 and 2.93, respectively (p < 0.0001). We found no significant differences between novice and veteran trainees regarding their training goal preferences (p = 0.07). Veteran trainees who had been in training for more than a year appeared to have higher self-efficacy since 31.16% reported receiving no supervision compared to 16.67% among novice trainees. In addition, people over 45 appear to have more health-related goals compared to their younger counterparts (p < 0.001). The quality of life scores of the trainees was related to their seniority in physical training, but only by a small magnitude (R2 = 0.06), p < .001). Those who trained in resistance training showed the greatest rate of adherence in relation to flexibility and aerobic training (p < 0.001), and women preferred more body toning and had more weight loss goals than men (p < 0.001). Discussion The results indicate that there are central and important factors that may affect adherence to physical activity, and that all these aspects must be taken into account when planning a training program or when there is a desire to maintain or increase adherence to physical activity. The research findings indicate that the main factors that can influence adherence to physical activity are identifying and increasing the trainee's self-efficacy, maintaining weekly training units with sufficient frequency to form a habit and incorporating resistance training into the training regime, as resistance training has shown high levels of adherence. Moreover, it seems that people with different degrees of experience in physical training have distinct and varied training goals, and there is no one goal that fits all. In addition, specific factors such as age and gender must also be taken into account, because the age and gender of the trainees may significantly affect the goals of physical training.